Pengaruh Konten Self-Healing Di Instagram Terhadap Kesehatan Mental Generasi Z Di Kota Bandung - Ageng Saepudin Kanda; Erwin firdaus (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to investigate the impact of self-healing content on Instagram on the mental health of generation Z in Bandung City. Through surveys and data analysis from generation Z respondents who were exposed to the content, this study concluded that self-healing content on Instagram had a significant positive influence on their mental health. Results show an increase in the level of mental well-being and stress management after exposure to self-healing content. Instagram, as a content delivery medium, proved to be effective in shaping positive perceptions and improving the mental health of Generation Z. These conclusions contribute to the understanding of the positive role of social media in supporting generation Z's mental well-being and provide a basis for further content development to improve their quality of life.